Correlation of axial length and corneal power with refractive status of patients with refractive error in Kano, North-Western Nigeria - Mahmud, Muhammad U.; Ibrahim, Umar F.; Isyaku, Mohammad; Hassan, Sadiq; Ebisike, Philips I.; Sani, Rabi Y. (International Journal of Research in Medical Sciences, 2024)
Background: Uncorrected refractive errors are a major cause of blindness and low vision. Determination of the etiology is essential in planning appropriate treatment modalities. Aim of this study was to determine the correlation between axial length and corneal power with refractive status of patients with refractive error in Kano, Nigeria. Methods: Observational cross-sectional study in which 385 eligible patients were recruited. Relevant history was obtained from the patients and ocular examination was done. Objective and Subjective refraction were performed. Spherical equivalent was calculated for patients with astigmatism. Keratometric readings (k1 and k2) and measurement of axial length were taken. Data was analyzed using the statistical package for the social sciences (SPSS) version 22. Results: Statistically significant inverse association (r=-1.7, r2=56.8%, p<0.0001) was found between Spherical equivalent objective refraction and axial length of right eye. Statistically significant inverse association (r=-1.2, r2=53.3%, p<0.0001) was found between Spherical equivalent subjective refraction and axial length of right eye. Statistically significant inverse association (r=-0.5, r2=8.5%, p<0.0001) was found between spherical equivalent objective refraction and corneal power of the right eye. Statistically significant inverse association (r=-0.3, r2=6.4%, p<0.0001) was found between spherical equivalent subjective refraction and Corneal power of right eye. Negative correlation existed between axial length and corneal power but was not statistically significant (r=-0.0, p<0.4). Conclusions: The study established that axial length and corneal power are the determinants of refractive status and that axial length is a stronger determinant.